A survey study of the transitioning towards high-value industrial product-services - Parida, Vinit; Sjödin, David Rönnberg; Wincent, Joakim; Kohtamäki, Marko (Elsevier, 2014)
Servitization literature suggests that traditional manufacturing companies are increasingly offering industrial services in order to increase their position in the global competition. However, little is known about extent and profit potential of different types of such offers in current industry. This paper offers an overview of such offers and concludes that maintenance based business models are most closely linked to increased revenue generation while add-on services have a negative effect. Future trends, suggest that business models such as R&D services and functional services will be increasingly important in the future.
Keywords: Servitization; Business Model; Manufacturing companies; Industrial Product Services; Financial Performance; fi=Johtaminen ja organisaatiot|en=Management and Organization|